Pemanfaatan Teknologi Augmented Reality Dalam Pemasaran Perumahan Mutiara Barangan Palembang - Pacu Putra; Akbar Alzaini; Rahmat Izwan Heroza; Allsela Meiriza (CESS (Journal of Computer Engineering, System and Science), 2021)
Perumahan Mutiara  Barangan is a housing complex that located at tanjung barangan, Palembang, Sumatera Selatan that was developed by PT. Kurnia Hamusri Sukses Mandiri. This This enterprise use pictures, brochures, and miniature for marketing activities. The objective of this research was to implement Augmented Reality Technology in digital marketing system to visualize their house in 3Ds View. The System Development model that used in this study is Multimedia Development Life Cycle (MDLC) which consists of concept, design, material collecting, assembly, testing and distribution. As a result of implementing Augmented Reality in Marketing of housing complex in Perumahan Mutiara Barangan Palembang can offer new experience of user in observing housing complex that was offered.